Peran Mahasiswa Kampus Mengajar Angkatan 4 dalam Meningkatkan Kompetensi SMPN Satu Atap Curug, Kota Serang - Nia Dwi Yuliastuti; Heni Pujiastuti (Dimasejati: Jurnal Pengabdian Kepada Masyarakat, 2023)
The Teaching Campus has entered its fourth batch, which is one of the Government's efforts to equalize education in Indonesia. The Teaching Campus involves all students from Sabang to Merauke with various majors to assist learning activities in schools. Student involvement aims to improve partner school competencies, especially literacy and numeracy competencies. In this case, students have a program in the form of teaching assistance, technology adaptation and school administration. With the presence of students, it is hoped that they can help schools in streamlining learning due to the past pandemic. This program is carried out at SMPN Satu Atap Curug school which is located at Kp. Cidadap, Tinggar Village, Curug District, Serang City, Banten with C accreditation.